Co-production of knowledge, degrees of openness and utility of science in non-hegemonic countries - Ferpozzi, Hugo Pablo (2019)
Collaboration in scientific knowledge production has been historically dominated and driven by hegemonic (Northern) countries, while non-hegemonic countries tend to take on secondary roles. The growing discourse on Open Science provides the opportunity to look critically at the roles and outcomes of collaborative knowledge creation. Drawing on four diverse case studies throughout Latin America, this project has sought to assess the ways that diverse actors, processes, and sectors converge to collaborate (willingly or not) on resolving social issues. Using Open Science as a theoretical framework, the chapter concludes with a summary of how different “types” of challenges may be more or less amenable to the collaborative practices of Open Science.